Sistema integrado de análise e distribuição de resultados aplicados à bebida de açaí - Koizimi, Sandra Maria Leandro (Universidade Federal de São Carlos, 2011)
The açaí palm (Euterpe oleracea Mart) is a tropical palm tree native to the Amazon. The main purpose of using the fruit is an açaí drink. It is estimated that the international açaí drink market grew 65% in the last three years, followed by the national market 55% and the metropolitan area of Belém 14% a year. The Brazil is the only exporter of this product, however açaí seeds are being planted in countries with similar climate. To raise the barrier to these new competitors is necessary to develop technological tools to guide the agricultural industry in the ongoing monitoring and quality improvement. The Near Infrared Spectroscopy (NIRS) has been established as an analytical technique using rapid response and therefore suitable for monitoring processes. Its spectrum can be related to physical variables and product quality. Among the variables used in the market are the dry matter content and anthocyanin content. This paper presents an indicator of competitive performance, constructed from regression models. It aims to establish a relationship between these variables and their NIR spectra, contrasting the conventional analytical methods currently used by agribusiness. This relationship is codified in a system using a free software platform, through the paradigm of object oriented programming.
Keywords: Biotecnologia; Espectroscopia no infravermelho próximo; Açaí; Orientação a objetos; NIRS; PLS; Antocianinas; Açaí; NIRS; PLS; Anthocyanins; Soluble solids; Object oriented; CIENCIAS BIOLOGICAS